2011
DOI: 10.5539/jas.v4n1p91
|View full text |Cite
|
Sign up to set email alerts
|

Beef Quality Assurance Injection Sites and Techniques

Abstract: Food safety has become a very important issue in our society. Modern livestock management practices rely upon the prudent use of injectable antibiotics and vaccines for the purpose of maintain herd health and productivity. Rasmussen (1980) concluded that both the active pharmaceutical and the carrier-vehicle administered are responsible for tissue injury. Now we need to put great emphasis on improper injections which can lead to trimming and discarding of expensive cuts, and learn to use a proper injection met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Since the risk of lesions in meat are considerably higher with intramuscular application (Li et al, 2012) and plasma alpha-tocopherol concentrations were not different between routes of application, it is concluded that subcutaneous administration is a practical alternative to the traditional intramuscular of administration of injectable vitamin E for feedlot cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Since the risk of lesions in meat are considerably higher with intramuscular application (Li et al, 2012) and plasma alpha-tocopherol concentrations were not different between routes of application, it is concluded that subcutaneous administration is a practical alternative to the traditional intramuscular of administration of injectable vitamin E for feedlot cattle.…”
Section: Resultsmentioning
confidence: 99%
“…The vaccine can be deposited under the subcutaneous tissue by reducing the compression force (transdermal NFI). Previous studies have suggested that NFI of vaccines could reduce the incidence of lesions at the vaccination site of animals (Chase et al, 2008; Li et al, 2011). However, Ko et al (2018) found no effect of intramuscular NFI on the incidence of lesions at the site of FMD vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…The vaccination is generally delivered with an injection because that has higher absorptivity than oral inoculation (Li et al, 2011). However, the vaccine administered by a needle syringe results in adverse effects such as pain, stress, broken needle residue in the carcass, tissue damage, and incidence of lesions at the injection sites such as neck and ham (Chase et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abattoir surveys in the USA beef industry have reported injection lesions incidences of 11.4% in 1995 decreasing to 2.1% in 2000 in top sirloin butts from fed steer and heifers [ 2 ]. A further review has further highlighted the economic importance of injection site lesions damage in beef cattle [ 3 ]. The incidence of abscesses or infection following injections in cattle is unknown.…”
Section: Introductionmentioning
confidence: 99%